'Enhanced Support for High Intensity Users of the Criminal Justice System': An Evaluation of Mental Health Nurse Input into Integrated Offender Management Services in the North East of England. Issue 1 (18th February 2015) - Dyer, Wendy; Biddle, Paul
Abstract : The current UK Government's focus on the development of services to manage and support offenders with mental health problems has resulted in a number of innovative project developments. This research examines a service development in the North East of England which co-located mental health nurses with two Integrated Offender Management teams. While not solving all problems, the benefits of co-location were clear, although such innovations are now at risk from government changes which will make Integrated Offender Management the responsibility of new providers without compelling them to co-operate with health services.